An extension of the identification algorithm for feedback active control of incomplete measured systems - Viet, La Duc; Anh, Nguyen Dong (Vietnam Journal of Mechanics, 2008)
In a previous paper [1], the identification algorithm is presented for feedback active controlled systems. However, this method can only be applied to complete measured systems. The aim of this paper is to present a combination of the identification algorithm and the modal superposition method to control the incomplete measured systems. The system response is expanded by modal eigenfunction technique. The external excitation acting on some first modes is identified with a time delay and with a small error depending on the sensor locations. Then the control forces will be generated to balance the identified excitations. A numerical simulation is applied to an eight story building subjected to base acceleration